Massive retroperitoneal hematoma as a complication of anticoagulation therapy in a patient treated in a pulmonary intensive care unit - Stjepanović, Mihailo; Buha, Ivana; Raljević, Snežana; Babić, Uroš; Savić, Milan; Mašković, Jovana; Roksandić, Marina; Marić, Dragana (Vojnosanitetski pregled, 2015)
Introduction. Retroperitoneal hematoma may occur as a result of trauma, but also from rupture of arterial aneurysms (aortic or iliac), surgical complications, tumors or anticoagulation therapy. Case report. We presented a patient on permanent anticoagulation therapy. On the day of admission to our institution, the patient had the value of his INR 5.57 which required immediate suspension of the therapy. The main symptom in this patient was pain in the right inguinal canal with propagation along the right leg, which was indicated in clinical picture of spontaneous retroperitoneal haematoma. After three days the fall of hemoglobin occurred, so the additonal diagnostics was done. A computed tomography of the abdomen was performed showing well limited, large retroperitoneal hematoma (213 ´ 79 ´ 91 mm). Transfusion of concentrated red blood cells was performed twice with satisfactory correction of hemoglobin level, and four units of fresh frozen plasma. The patient was hemodynamically stabilized and discharged after a two-month long intensive care unit treatment, with the advice to use low-molecular weight heparin 2 ´ 0.4 mg subcutaneusly, due to persistent arrhythmia. Conclusion. In patients on anticoagulation therapy regular monitoring of the anticoagulant status is extremely important, because of the possibility of fatal complications development, such as retroperitoneal hematoma.
Keywords: anticoagulants; drug toxicity; hemorrhage; hematoma; retroperitoneal space; treatment outcome